Evaluation of a local goat population for fertility traits aiming at the improvement of its economic sustainability through genetic selection - Atoui, Ahlem; Carabaño, María J.; Najari, Sghaier (Spanish Journal of Agricultural Research, 2018)
The study aims to determine the environmental and genetic components for the reproductive performance of a Tunisian local goat population to set up the basis for the future improvement of this important component of efficient production. The reproductive traits considered were kidding interval (KI) and litter size at birth (LSB). Records of 462 kiddings belonging to 185 dams and 11 sires were collected over a period of 22 years in the caprine herd of the Arid Areas Institute of Médenine. Significance of environmental effects was tested with ANOVA techniques. Genetic parameters were estimated using restricted maximum likelihood fitting an animal mixed model. Mean KI and LSB were 13.85 ± 5.20 months and 1.33 ± 0.49 kids, respectively. The effect of parity number and the interaction between year and month of kidding were significant for LSB and KI. Trait LSB increased with parity number up to the fifth parity while KI decreased with parity number indicating that young females show compromised reproductive performance probably because of growth requirements and scarcity of food resources. A detrimental effect for kiddings occurring during winter (matings in summer) was observed from estimates of the year by month of kidding effect. Heritability estimates for KI and LSB were 0.13 and 0.08, respectively. A moderate repeatability estimate of 0.31 was obtained for LSB while 0.17 was obtained for KI. The low estimates of heritability obtained for reproductive traits indicated that accurate selection based on the doe’s own performance will require large amounts of data. However, the estimated genetic variability was substantial, providing the grounds for the genetic improvement of the reproductive parameters in this population.